Digital Capitalism. Media, Communication and Society Volume Three - Fuchs, Christian

Which “motionese” parameters change with children's age? Disentangling attention-getting from action-structuring modifications - Rohlfing, Katharina J.; Vollmer, Anna-Lisa; Fritsch, Jannik; Wrede, Britta (Frontiers in Communication)
Modified action demonstration—dubbed motionese— has been proposed as a way to help children recognize the structure and meaning of actions. However, until now, it has been investigated only in young infants. This brief research report presents findings from a cross-sectional study of parental action demonstrations to three groups of 8–11, 12–23, and 24–30-month-old children that applied seven motionese parameters; a second study investigated the youngest group of participants longitudinally to corroborate the cross-sectional results. Results of both studies suggested that four motionese parameters (Motion Pauses, Pace, Velocity, Acceleration) seem to structure the action by organizing it in motion pauses. Whereas these parameters persist over different ages, three other parameters (Demonstration Length, Roundness, and Range) occur predominantly in the younger group and seem to serve to organize infants' attention on the basis of movement. Results are discussed in terms of facilitative vs. pedagogical learning.

Interactive Robot Task Learning: Human Teaching Proficiency With Different Feedback Approaches - Hindemith, Lukas; Bruns, Oleksandra; Noller, Arthur Maximilian; Hemion, Nikolas; Schneider, Sebastian; Vollmer, Anna-Lisa (IEEE Transactions on Cognitive and Developmental Systems)

The smoots Package in R for Semiparametric Modeling of Trend Stationary Time Series - Feng, Yuanhua; Gries, Thomas; Letmathe, Sebastian; Schulz, Dominik (The R Journal)
Keywords: Statistics; Probability and Uncertainty; Numerical Analysis; Statistics and Probability

Geschichten im Wandel: Neue Perspektiven für die Erinnerungskultur in der Migrationsgesellschaft (Public History - Angewandte Geschichte)

Stuhlmann-Laeisz, Gottlob Freges "Grundgesetze der Arithmetik". Ein Kommentar des Vorworts, des Nachworts und der einleitenden Paragrafen, mentis Verlag: Paderborn 2020 - Peckhaus, Volker (zbMATH Open, Zbl 1481.01035)

Neuwirth, Stefan, “Lorenzen’s Reshaping of Krull’s Fundamentalsatz for Integral Domains (1938–1953)”, in: Gerhard Heinzmann et al. (eds.), Paul Lorenzen – Mathematician and Logician, Springer: Cham 2021 (Logic, Epistemology, and the Unity of Science; 51), 143–183. - Peckhaus, Volker (zbMATH Open, Zbl 1484.01013)

Tait, W.W., “Kant on Number”, in: Carl Posy et. al. (eds.), Kant’s Philosophy of Mathematics, Vol. 1: The Critical Philosophy and its Roots, Cambridge University Press: Cambridge 2020, 267–291 - Peckhaus, Volker (zbMATH Open, Zbl 1495.01012)

Warren, Daniel, "Kant on Mathematics and the Metaphysics of Corporal Nature. The Role of the Infinitesimal”, in: Carl Posy et. al. (eds.), Kant’s Philosophy of Mathematics, Vol. 1: The Critical Philosophy and its Roots, Cambridge University Press: Cambridge 2020, 66–82 - Peckhaus, Volker (zbMath Open, Zbl 1492.01011)

Antos, Carolin, “Conceptions of Infinity and Set in Lorenzen’s Operationist System”, in: Gerhard Heinzmann et al. (eds.), Paul Lorenzen – Mathematician and Logician, Springer: Cham 2021 (Logic, Epistemology, and the Unity of Science; 51), 23–46. - Peckhaus, Volker (zbMATH Open, Zbl 1494.03011)

Coquand, Thierry, “Lorenzen and Constructive Mathematics”, in: Gerhard Heinzmann et al. (eds.), Paul Lorenzen – Mathematician and Logician, Springer: Cham 2021 (Logic, Epistemology, and the Unity of Science; 51), 48–61. - Peckhaus, Volker (zbMath Online, Zbl 1490.03001)

Luna, Laureano. “Strengthening the Russellian Argument Against Abolutely Unrestricted Quantification”. Synthese 200 (2022), No. 3, Paper No. 182, 13 pp - Peckhaus, Volker (Mathematical Reviews, MR4410107)

Scholz, Heinrich - Peckhaus, Volker (Stanford Encyclopedia of Philosophy)

Ready-to-eat-cereal intake and long term body weight status among children and adolescents – results of the DONALD Study - Hornemann, Stephanie; Jankovic, Nicole; Perrar, Ines; Längler, Alfred; Hohoff, Eva; Alexy, Ute
Abstract The aim of this study is to analyse the association between RTEC (Ready-To-Eat-Cereals) intake and long-term changes in Standard Deviation Score of Body Mass Index (BMI-SDS) and Fat Mass Index (FMI) among children and adolescents in Germany. Overall, 4,920 3-day dietary records and anthropometric measurements of 721 DONALD (Dortmund Nutritional and Anthropometric Longitudinally Designed Study) participants (3.5–18.5 years; boys: 52%) kept in 2004–2018 were analysed using polynomial mixed-effects regression models. There was no statistically significant association between RTEC or RTEC meal intake and BMI-SDS as well as FMI, probably due to the overall low RTEC intake.

Associations of chronotype and social jetlag with eating jetlag and their changes among German students during the first COVID-19 lockdown. The Chronotype and Nutrition study - Stutz, B.; Buyken, A.E.; Schadow, A.M.; Jankovic, N.; Alexy, U.; Krueger, B. (Appetite)

Changes in Total Energy, Nutrients and Food Group Intake among Children and Adolescents during the COVID-19 Pandemic—Results of the DONALD Study - Perrar, Ines; Alexy, Ute; Jankovic, Nicole (Nutrients)
The COVID-19 pandemic may have changed the habitual lifestyles of children and adolescents, in particular, due to the closure of kindergartens and schools. To investigate the impact of the pandemic on nutrients and food intake of children and adolescents in Germany, we analyzed repeated 3-day weighed dietary records from 108 participants (3–18 years; females: n = 45, males: n = 63) of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study. Polynomial mixed-effects regression models were used to identify prospective changes in dietary intake (total energy (TEI), carbohydrates, fat, protein, free sugar, ultra-processed foods, fruits and vegetables, sugar sweetened beverages and juices) before and during the first months of the COVID-19 pandemic. For the current analysis, we have chosen the first months of the pandemic (March 2020–August 2020), as this was the period with the most restrictions in Germany so far (kindergarten, school and restaurant closures; contact and outdoor activity restrictions). No significant changes in either the selected nutrients or food groups were observed. However, children and adolescents recorded a significantly lower TEI during the pandemic (β = −109.65, p = 0.0062). Results remained significant after the exclusion of participants with under-reported records (β = −95.77, p = 0.0063). While macronutrient intake did not change, descriptive data indicate a non-significant decrease in sugar sweetened beverages and ultra-processed foods intake. We suggest that children and adolescents from high socioeconomic families may have adapted lifestyle changes during the pandemic.

Fermüller, Christian G., "Connecting Sequent Calculi with Lorenzen-Style Dialogue Games", in: Gerhard Heinzmann et al. (eds.), Paul Lorenzen – Mathematician and Logician, Springer: Cham 2021 (Logic, Epistemology, and the Unity of Science; 51), 143–183 - Peckhaus, Volker (zbMATH Open, Zbl 1490.03014)

De Mol, Liesbeth/Maarten Bullynck,, “Making the History of Computing. The History of Computing in the History of Technology and the History of Mathematics”, Revue de Synthèse (7) 139 (2018), 361-380 - Peckhaus, Volker (Mathematical Reviews, MR4162129)

Third‐Order Susceptibility of Lithium Niobate: Influence of Polarons and Bipolarons - Kozub, Agnieszka L.; Gerstmann, Uwe; Schmidt, Wolf Gero (physica status solidi (b))
The third‐order susceptibility of lithium niobate (LiNbO 3 ) is calculated within a Berry‐phase formulation of the dynamical polarization based on the electronic structure obtained within density‐functional theory (DFT). Maximum values of the order of m V are calculated for photon energies between 1.2 and 2 eV, i.e., in the lower half of the optical bandgap of lithium niobate. Both free and bound electron (bi)polarons are found to lead to a remarkable enhancement of the third‐order susceptibility for photon energies below 1 eV.

Christian Thiel, Fregeana. Zwölf Studien über Freges Logik
XII + 247 S. Rezension: Dókos. Revista filosófica 31–32 (2023), 275–281 (J. Padilla Gálvez)